Analisis Minat Masyarakat Terhadap Perbankan Syariah - Syamsurizal Syamsurizal; Sherlya Putri; Mega Adyana Movitaria; Novi Yanti (Hikmah, 2022)
This study aims to analyze public interest in Islamic banking, focusing on analysing the community's response to socialization by Islamic banks. This study uses qualitative methods with a phenomenological approach. This research was conducted in the Nagari Malai III Koto community, Sungai Geringging District, Padang Pariaman. Research informants are people who use the services of Islamic banks. Collecting data using observation techniques, interviews, and documentation studies. Data analysis uses data reduction flow, data presentation, and conclusion drawing. The results of the study revealed that the public's interest in choosing Islamic banks, including: (1) there is no monthly administration fee like in conventional banks, (2) this is known from Riba because Islamic banks use a profit-sharing system like general trading, (3) fees cheap transactions, (4) benefit from the profit-sharing system carried out by Islamic banks, (5) are interested in Islamic bank products such as savings for hajj, umroh, qurban, and endowments. Then the community's response to the socialization carried out by Islamic banks is still not interesting, this is due to the lack of optimal socialization carried out by Islamic banks, and this is evident from the large number of people who do not understand the products offered by Islamic banks.